Process Performance with DC Current in Treatment of Poultry Slaughterhouse Wastewater Using Aluminum Electrodes - Zabiholllah Yousefi; Hossein Sahebian; Abdoliman Amouei; Reza Ali Mohammadpour; Ebrahim Zarei (Journal of Mazandaran University of Medical Sciences, 2019)
Background and purpose: Poultry slaughterhouses produce high rates of polluted effluent. They can contaminate the environment if not treated properly. This study aimed at investigating the performance of electrocoagulation process with direct (DC) current in treatment of poultry slaughterhouse effluent using aluminum electrodes. Materials and methods: This study was performed as an experimental study on a pilot scale on poultry slaughterhouse effluent. In this experiment, direct flow and four aluminum electrodes, which were spaced two centimeters apart, were used as monopole. We investigated the percentage of organic load waste removal (COD, BOD5) and different pH changes, at 6, 12, and 18 V, and pH 3, 5, 7, and 9, and different reaction times (10, 30, 60, 90 min). Results: The removal efficiency of COD and BOD5 using DC current was optimally at 18 V and pH=7 that occurred in 45 min (84.86%, 88.93%, respectively). Final pH was found to be 8.47. Conclusion: According to current findings, electrocoagulation process can be used as a combined process with high efficiency in removal of slaughterhouse effluent contaminants, so, using this technique can produce wastewater according to the standards.